Pengaruh Edukasi Dengan Media Video Tentang ASI Eksklusif Melalui Aplikasi Whatsapp Terhadap Ibu Menyusui di Wilayah Kerja Puskesmas Banyuanyar Surakarta - Abdilla Fi Qisthy Wibowo; Kuswati Kuswati; Henik Istikhomah (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Exclusive breast milk is breast milk given to a newborn baby in the first six months without any additional food. Lack of knowledge about exclusive breastfeeding has an impact on mothers' low ability to provide exclusive breastfeeding to their babies. Efforts to increase the knowledge and attitudes of breastfeeding mothers regarding exclusive breastfeeding can be done by providing education using video media via the WhatsApp application. To determine the effect of education using video media about Exclusive Breastfeeding via the WhatsApp application on the knowledge and attitudes of breastfeeding mothers in the Banyuanyar Surakarta Community Health Center working area. This research uses a Quasi Experimental Design research design with a One Group Pretest Posttest Design. The sampling technique was purposive sampling with 45 breastfeeding mothers in the working area of ​​the Banyuanyar Community Health Center, Surakarta. Data analysis used the Wilcoxon Test and Paired T Test. The results showed that there was an increase in the average knowledge after the intervention from 13.78 to 19.33 and there was an increase in the average attitude after the intervention from 54.47 to 68.51. The results of the Wilcoxon test showed that there was an increase in knowledge after the intervention, p = 0.000 (p value < 0.05) and the results of the paired T test showed an increase in attitudes after the intervention, p = 0.000 (p value < 0.05). Providing education using video media about exclusive breastfeeding via the WhatsApp application has an impact on the knowledge and attitudes of breastfeeding mothers in the Banyuanyar Surakarta Community Health Center working area.